Rigidoporus microporus and the white root rot disease of rubber - Saidi, Noor Baity; Al-Obaidi, Jameel R.; Che Fisol, Ahmad Faiz (John Wiley & Sons, 2023)
Rigidoporus microporus is an economically important plant pathogenic fungus causing particularly severe losses to the rubber industry worldwide. The pathogen is responsible for white root rot (WRR) disease, infecting the host roots via white fibrous mycelia, causing vascular disfunction, and visible symptoms including leaf discolouration and dieback in severely infected trees. The final stage of the disease is characterized by the appearance of basidiocarps at the tree collar. The development of WRR in rubber plantations is dependent on fungal diversity in the soil, pH, temperature, and cation levels. Several ‘-omics’ approaches have been undertaken to understand how R. microporus functions with the objective, ultimately, to control WRR. Unfortunately, no resistant rubber clone has been identified to date. The disease is managed through physical and chemical methods that are laborious and negatively impact the environment, respectively. Recent developments in research on R. microporus shed light on potential sustainable routes to WRR disease control using beneficial microorganisms and natural compounds. This review discusses the characteristics of R. microporus isolates from different geographical origins, the pathogenicity and virulence mechanisms of the necrotrophic fungal pathogen, factors that influence the development of WRR, recent findings from the multi-omics studies, and control methods that are availableto combat this economically important pathogen.